Factor reallocation and cost pass-through under the carbon emission trading policy: Evidence from Chinese metal industrial chain. (1st July 2022) - Zou, Han; Zhong, Mei-Rui
Abstract: Piloted in 2013, the Carbon Emission Trading (CET) policy is the most practical tool for emission reduction in China, however, midstream firms increase capital investment to cope with compliance costs, resulting in more expensive intermediate commodities that may hurt export benefits of industrial chain terminal. Based on the A-shared listed firms of Chinese metal industrial chain during 2008–2018, this paper applies the difference-in-difference model to explore the effects of CET on chain reactions of corporate activities. After a set of robustness tests, the results show that midstream firms accelerate capital deepening in response to CET and become more capital-intensive, but gain losses of outputs both in revenue and in quantity, accompanying cost pass-through to downstream firms, which are all contributed by the external pressure imposed by stakeholders and internal incentive from senior managers. Then, affected by price fluctuation in markets of production factors and carbon-intensive commodities, CET increases the cleanliness standards of midstream firms and promote their export benefits immediately, and cost pass-through generates more expensive intermediate products and results in export contraction of downstream firms, but precision machine manufacturing has seen export growth, as their products are more sensitive to technological breakthroughs than material costs. Graphical abstract: Image 1 Highlights: Midstream firms conduct capital deepening and become more capital-intensive. Compliance costs transfer to downstream firms along metal industrial chain. Export benefits increase in midstream firms but decrease in downstream firms. Corporate activities are driven by internal incentive and external pressure. Export benefits of downstream firms in precision machinery manufacturing increase.